(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
The overarching goal of this article is to analyze the discourse that Narcissus Zmichowska used in her work. In the text I focus on the author’s approach to the “women’s question”, so the main analytical tool turns out to be feminist criticism. Due to the many areas of the writer’s activity looked at, the text is divided into parts. The first is an introduction, where women’s work is admonished, the next is a reminder of the silhouette of Zmichowska. The fourth part of the article talks about the differences in the understanding of womanhood between the author under discussion and her teacher – Klementyna Hoffmanowa, née Tańska. The next one moves to the writer’s works, more precisely to the novel Poganka, where the book’s heroine Aspasia is discussed. The last analytical section is devoted to a look at Zmichowska’s epistolography. The article closes with a conclusion highlighting the precocity of the author undertaken.